1998
DOI: 10.1016/s0014-5793(97)01575-5
|View full text |Cite
|
Sign up to set email alerts
|

Specific gene blockade shows that peptide nucleic acids readily enter neuronal cells in vivo

Abstract: Peptide nucleic acids (PNAs) are DNA analogs that can hybridize to complementary sequences with high affinity and stability. Here, we report the first evidence of intracellular delivery of PNAs in vivo. Two CNS receptors, an opioid (mu) and a neurotensin (NTR-1), were targeted independently by repeated microinjection of PNAs into the periaqueductal gray. Behavioral responses to neurotensin (antinociception and hypothermia) and morphine (antinociception) were lost in a specific manner. Binding studies confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(39 citation statements)
references
References 27 publications
4
35
0
Order By: Relevance
“…Some of these effects are likely mediated via NTS1, because mice deficient in NTS1 expression exhibited reduced antinociception in the hotplate test (Tyler et al, 1998;Pettibone et al, 2002). However, the extensive anatomical association found here between NTS2 and spinal nociceptive pathways, together with the evidence for a role of NTS2 in the mediation of the supraspinal analgesic actions of NT (Dubuc et al, 1999;Maeno et al, 2004), prompted us to investigate whether this receptor subtype might also be involved in the mediation of the antinociceptive effects of NT at the spinal level.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Some of these effects are likely mediated via NTS1, because mice deficient in NTS1 expression exhibited reduced antinociception in the hotplate test (Tyler et al, 1998;Pettibone et al, 2002). However, the extensive anatomical association found here between NTS2 and spinal nociceptive pathways, together with the evidence for a role of NTS2 in the mediation of the supraspinal analgesic actions of NT (Dubuc et al, 1999;Maeno et al, 2004), prompted us to investigate whether this receptor subtype might also be involved in the mediation of the antinociceptive effects of NT at the spinal level.…”
Section: Discussionmentioning
confidence: 95%
“…Two of these, NTS1 and NTS2, correspond to G-protein-coupled receptors, whereas the third one, NTS3, is a single transmembrane spanning receptor that shares 100% homology with the sorting protein, gp95/sortilin (Hermans and Maloteaux, 1998;. Although some of the antinociceptive effects of NT appear to be exerted through the highaffinity NTS1 receptor (Tyler et al, 1998;Pettibone et al, 2002), the fact that various NT analogs exhibit analgesic potencies that do not correlate with their binding affinity for NTS1 suggests that other receptors are also involved. Several lines of evidence point to the levocabastine-sensitive low-affinity NTS2 subtype as a pos-sible antinociceptor .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A role for NTR2 in NT-induced analgesia (but not hypothermia) was further suggested by Dubuc et al (1999b) by using an NTR2 antisense knock-down strategy. On the other hand, use of peptide nucleic acids to downregulate NTR1 expression provided evidence for involvement of NTR1 in the antinociception and hypothermia (Tyler et al, 1998a). Other studies showed that the highly NTR2-selective levocabastine had no effect on baseline core body temperature or NT-induced hypothermia or baseline analgesia (Tyler et al, 1998b;Dubuc et al, 1999a), but either partially inhibited NT-induced analgesia at low (but not high) doses (Tyler et al, 1998b) or completely blocked it (Dubuc et al, 1999a).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in a very exciting and controversial study Richelson and coworkers have claimed that antigene and antisense PNA can pass the blood-brain barrier and can bind in-vivo to the neurotensin receptor (NTR1) in rats [52,53]. Specifically, intraperitoneal injection of PNA inhibited the hypothermic and antinociceptive activities of neurotensin microinjected in the brain.…”
Section: Pna As a Regulator Of Gene Expressionmentioning
confidence: 99%